Thermodynamics of HMGB1 interaction with duplex DNA. - Müller, S; Bianchi, M; Knapp, S (2001)
The high mobility group protein HMGB1 is a small, highly abundant protein that binds to DNA in a non-sequence-specific manner. HMGB1 consists of 2 DNA binding domains, the HMG boxes A and B, followed by a short basic region and a continuous stretch of 30 glutamate or aspartate residues. Isothermal titration calorimetry was used to characterize the binding of HMGB1 to the double-stranded model DNAs poly(dAdT).(dTdA) and poly(dGdC).(dCdG). To elucidate the contribution of the different structural motifs to DNA binding, calorimetric measurements were performed comparing the single boxes A and B, the two boxes plus or minus the basic sequence stretch (AB(bt) and AB), and the full-length HMGB1 protein. Thermodynamically, binding of HMGB1 and all truncated constructs to duplex DNA was characterized by a positive enthalpy change at 15 degrees C. From the slopes of the temperature dependence of the binding enthalpies, heat capacity changes of -0.129 +/- 0.02 and -0.105 +/- 0.05 kcal mol(-1) K(-1) were determined for box A and full-length HMGB1, respectively. Significant differences in the binding characteristics were observed using full-length HMGB1, suggesting an important role for the acid tail in modulating DNA binding. Moreover, full-length HMGB1 binds differently these two DNA templates: binding to poly(dAdT).(dTdA) was cooperative, had a larger apparent binding site size, and proceeded with a much larger unfavorable binding enthalpy than binding to poly(dGdC).(dCdG).